The Instructional Leadership Role of Superintendents in Instructionally Effective School Districts - Bjork, Lars G. (Advances in Social Sciences Research Journal, 2024)
Throughout the past four decades (1983-2024), the rise of a global economy and the changing nature of American society underscored the importance of educating all children. Successive waves of education reform in the United States of America (USA) launched a wide array of initiatives focused on improving student learning. These state and federal policy initiatives were accompanied by an historic shift in role expectations of school district superintendents. An examination of trend data reported in three successive nation-wide reports released by the American Association of School Administrators (AASA) for the years 2000, 2010 and 2020 (Glass, Björk & Brunner, 2000; Kowalski, et al., 2011; Tienken, 2021) suggest that role expectations for district superintendents moved from away from an emphasis on management to a focus on instructional leadership. In addition, findings on superintendent instructional leadership practices in Instructionally Effective School Districts (IESD) reported by Bjork (1993, 2010, 2024) and Bjork & Browne-Ferrigno (2014) note that they effectively used their managerial position to support district-wide instructional improvement. They found that superintendents serving in IESD school districts used enacted their management responsibilities in areas that would indirectly influence the quality of learning and teaching including: (1) Staff selection and recruitment; (2) Principal supervision and evaluation; (3) Establishing clear instructional and curricular goals; (4) Monitoring learning and curricular improvement activities and, (5) Financial planning for instruction. These findings suggest that IESD superintendents’ use their management prerogatives to enact their instructional leadership role and reframe school district leadership for deeper learning in next generation schools.